2007
DOI: 10.1002/jcd.20167
|View full text |Cite
|
Sign up to set email alerts
|

Partitions of finite vector spaces into subspaces

Abstract: Let V n (q) denote a vector space of dimension n over the field with q elements. A set P of subspaces of V n (q) is a partition of V n (q) if every nonzero element of V n (q) is contained in exactly one element of P. Suppose there exists a partition of V n (q) into x i subspaces of dimension n i , 1 ≤ i ≤ k. Then x 1 , . . . , x k satisfy the Diophantine equation(q n i − 1)x i = q n − 1. However, not every solution of the Diophantine equation corresponds to a partition of V n (q). In this article, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…In [5], when q = 2 and n = dim(V ) ≤ 7, we found all solutions to the Diophantine equation (1) with n 1 > · · · > n k for which there exists a partition of V (Heden [8] had settled the n = 6 case in 1986). In [6], we showed that if n > 2, and x and y are nonnegative integers satisfying x(2 3 − 1) + y(2 2 − 1) = 2 n − 1, then there exists a partition of V n (2) …”
Section: Lemma 13 (Bumentioning
confidence: 96%
“…In [5], when q = 2 and n = dim(V ) ≤ 7, we found all solutions to the Diophantine equation (1) with n 1 > · · · > n k for which there exists a partition of V (Heden [8] had settled the n = 6 case in 1986). In [6], we showed that if n > 2, and x and y are nonnegative integers satisfying x(2 3 − 1) + y(2 2 − 1) = 2 n − 1, then there exists a partition of V n (2) …”
Section: Lemma 13 (Bumentioning
confidence: 96%
“…Heden [11] gave lower bounds for the number of subspaces of least dimension in a given partition of V (n, q). The 4 6 3 21 2 6 -partition of V (8,2) in Example 17 shows that the bound in Theorem 1 (iii) from [11] is tight.…”
Section: Proof Of Theoremmentioning
confidence: 87%
“…(8,2) with (a, b, c) = (13,6,6). We then show in Section C that there is no 4 13 3 6 2 6 -partition of V (8,2).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations